Short-Term Outcomes following “Switching” to Monthly Ranibizumab in Neovascular Age-Related Macular Degeneration Showing Insufficient Response to Bimonthly Aflibercept - Jong Suk Lee; Hyun Goo Kang; Christopher Seungkyu Lee; Se Joon Woo (Journal of Ophthalmology)
Background/Objectives. To evaluate the efficacy of switching to monthly ranibizumab in neovascular age-related macular degeneration (nAMD) showing an insufficient response to bimonthly aflibercept. Subjects/Methods. A total of 13 nAMD eyes showing an insufficient treatment response to three successive aflibercept injections were enrolled through a retrospective chart review. After switching, three consecutive monthly intravitreal ranibizumab injections were performed. The main outcome measurements included the best-corrected visual acuity (BCVA), central retinal thickness (CRT), presence of intraretinal fluid (IRF), and subretinal fluid (SRF) using optical coherence tomography (OCT) and were measured every month. Results. CRT and logMAR VA were 349.62 ± 223.51 μm and 0.50 ± 0.23 at the baseline and 274.69 ± 148.77 μm and 0.46 ± 0.24, 311.54 ± 192.90 μm and 0.45 ± 0.20 at 1 month after the first and third ranibizumab injections, respectively. The CRT decrease during three ranibizumab injections was statistically significant (38.08 ± 69.52 μm, p=0.033). Change in VA was not statistically significant. The percentage of eyes with SRF was 100% at baseline and 53.8%, 76.9%, and 69.2% one month after each ranibizumab injections. The percentage of eyes with IRF was 38.5% at baseline and 23.1%, 23.1%, and 15.4%, respectively, after switching. Conclusion. Switching to monthly ranibizumab in nAMD showing an insufficient response to bimonthly aflibercept led to immediate anatomical improvement. It can be considered in countries where the healthcare insurance system limits the minimum injection interval of aflibercept.